Die Missionsstation Makkovik über den Wald hinweg die Bucht zu gesehen : [ca. 1901] - Schmitt, Christian, 1868-1933. (2001)
Black and white photograph of the mission station at Makkovik and the bay, circa 1901. Black and white photograph of the mission station at Makkovik and the bay, circa 1901.